Low pretreatment prognostic nutritional index predicts poor survival in breast cancer patients: A meta-analysis - Hu, Guoming; Ding, Qiannan; Zhong, Kefang; Wang, Shimin; Wang, Songxiang; Huang, Liming (PloS one, 2023)
Prognostic nutritional index (PNI), as an indicator of nutritional immune status, has been shown to be associated with therapeutic effects and survival of solid tumors. However, the prognostic role of PNI before treatment in human breast cancer (BC) is still not conclusive. Hence, we performed this meta-analysis to assess the value of it in prognosis prediction for BC patients. We searched PubMed, Embase, Web of Science and EBSCO to identify the studies evaluating the association between PNI and survival such as overall survival (OS), disease-free survival (DFS) of BC, and computed extracted data into hazard ratios (HRs) for OS, DFS and clinicopathological features with STATA 12.0. A total of 2322 patients with BC from 8 published studies were incorporated into this meta-analysis. We discovered that low pretreatment PNI was significantly associated with worse OS, but not with DFS in BC patients. In stratified analyses, the result showed that decreased PNI before treatment was remarkably related with lower 3-year, 5-year, 8-year and 10-year OS, but not with 1-year survival rate in BC. In addition, although reduced PNI could not impact 1-year, 3-year or 5-year DFS, it considerably deteriorated 8-year and 10-year DFS in patients. Low pretreatment PNI deteriorated OS, 8-year and 10-year DFS in BC patients, implicating that it is a valuable prognostic index and improving the nutritional immune status may offer a therapeutic strategy for these patients.